Psychometric testing in Portuguese of Helsinki's chronic pain index for dogs with chronic signs of osteoarthritis - Matsubara, L. M. [UNESP]; Luna, S. P. L. [UNESP]; Teixeira, L. R. [UNESP]; Castilho, M. S. [UNESP]; Bjorkman, A. H.; Oliveira, H. S. [UNESP]; Anunciacao, L. F. C. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2019)
We aimed to determine validity, reliability, and sensitivity of Helsinki's chronic pain index (HCPI) and stablish a correlation between HCPI in dogs with hip dysplasia (HD) using pressure sensitive walkway. Forty-owners of dogs with HD and 16 owners of health dogs filled a questionnaire. Dogs with HD were treated with carprofen 4.4mg/ kg (GT n=21) or with placebo (GP n=19), both were administered once a day for 4 weeks. Evaluation was performed by the owners using the questionnaire (HCPI), the Visual Analogue Scale for pain (VASpain) and the VAS for locomotion (VASloc). The evaluation was performed 2 weeks before the treatment began (A1), immediately after treatment (A2), two (S2), four (S4) and two weeks after the end of treatment (S6) and the lameness was evaluated by pressure sensitive walkway. The internal consistency of the data was considered excellent (Cronbach alpha coefficient=0.89). There was a moderate correlation between the HCPI and VASpain. For VASloc the correlation was good. However, there was no difference between treatments, indicating low sensibility. No correlation was observed between pressure sensitive walkway and HCPI. We concluded that the questionnaire has construct and criterion validity, reliability and can be applied in dogs with osteoarthritis in Portuguese-speaking countries.
Keywords: dogs; chronic pain; osteoarthritis; validation studies